웃음요법 프로그램이 간호대학생의 지각된 스트레스와 우울에 미치는 효과 - 임소연(So-Youn Yim); 박민희(Min-Hee Park) (한국콘텐츠학회 논문지, 15(11), 2015)
The purpose of this study was to examine the effects of laughter therapy program on stress and depression in nursing college students. The design of this study is nonequivalent control group, quasi-experimental study. Data were collected from December 5, 2014, to January 9, 2015, with 75 nursing sophomores (40 in experimental group and 35 in control group) in Chungnam and Jeonbuk Province in Korea, using self-reported questionnaires. The experimental group participated in laughter therapy program four times, once a week for 120min per session. The data were collected prior and after the intervention using self-administered questionnaires. Data were analyzed using t-test and $X^2-test$. The results of the study showed that the levels of stress (t=-2.32, p=0.02) and depression (t=-4.87, p<0.001) were significantly lower in the experimental group than in the control group. Based on the results, the laughter therapy program may be recommended as an useful intervention to effectively reduce the levels of stress and depression in nursing college students and anticipated to be developed and published continuously. 본 연구는 웃음요법 프로그램이 간호대학생의 지각된 스트레스와 우울 정도에 미치는 효과를 확인하기 위한 비동등성 대조군 전 후 유사 실험 설계이다. 연구 대상자는 충남지역에 위치한 B대학과 전북지역에 위치한 W대학의 간호학과 학생들로 실험군 40명, 대조군 35명이었고, 자료수집기간은 2014년 12월 5일부터 2015년 1월 9일까지였다. 웃음요법 프로그램은 1차시 당 2시간씩 1주 간격 으로 총 4차례의 프로그램이 진행되었으며, 자료 수집은 실험군과 대조군에게 사전-사후 자기기입식 설문방법으로 진행하였다. 자료 분석방법은 t-test와 $X^2-test$ 분석을 이용하였고, 연구결과에서 실험군은 사전에 비해 사후에 지각된 스트레스(t=-2.32, p=.02)와 우울 점수가(t=-4.87, p<.001) 유의하게 감소되었다. 본 연구 결과를 토대로 웃음요법 프로그램이 간호대학생에게 스트레스와 우울을 중재하기 위한 효과적인 프로그램인 것을 확인하였고, 추후 연속적으로 체계적인 웃음요법 프로그램의 구성 개발 및 시행을 기대한다.